2021
DOI: 10.1039/d0nr08936b
|View full text |Cite
|
Sign up to set email alerts
|

The detrimental invasiveness of glioma cells controlled by gadolinium chelate-coated gold nanoparticles

Abstract: Glioblastoma are characterized by an invasive phenotype, which is thought to be responsible for recurrences and the short overall survival of patients. In last decade, the promising potential of ultrasmall...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Recently, we have demonstrated on glioblastoma cells grown as monolayers that Au@DTDTPA(Gd) uptake induced a marked increase of the Young’s modulus measured by atomic force microscopy and a decreased number of protrusions, causing an increased cell stiffness and impaired cell motility. 16 In the present study, when U87 spheroids were treated by RT+NPs, the living escaped cells appeared unable to form the interconnected network and we assume that similar mechanisms were involved. Moreover, living escaped cells exhibited reduced metalloprotease activity in RT+NPs groups.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Recently, we have demonstrated on glioblastoma cells grown as monolayers that Au@DTDTPA(Gd) uptake induced a marked increase of the Young’s modulus measured by atomic force microscopy and a decreased number of protrusions, causing an increased cell stiffness and impaired cell motility. 16 In the present study, when U87 spheroids were treated by RT+NPs, the living escaped cells appeared unable to form the interconnected network and we assume that similar mechanisms were involved. Moreover, living escaped cells exhibited reduced metalloprotease activity in RT+NPs groups.…”
Section: Discussionmentioning
confidence: 51%
“…Au@DTDTPA(Gd) nanoparticles were synthesized and characterized as previously described in our published work. 16 For a typical preparation of gold nanoparticles, HAuCl 4 ·3H 2 O (200 mg, 51×10 −5 mol) was placed in a 250 mL round-bottom flask and was dissolved with methanol (60 mL). In another flask, DTDTPA (256 mg, 50×10 −5 mol), water (40 mL) and acetic acid (2 mL) were mixed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma stem cells, which are extremely invasive, aggressive, and therapy-resistant, make up the glioma cells. They are thus distinguished by an invasive phenotype with strong migratory potential [ 94 ]. As a result, it is claimed that encapsulating various treatments into polymeric micelles will increase drug transport across the BBB.…”
Section: General Issues and Status Quo Of Polymeric Micellesmentioning
confidence: 99%
“…Au@DTDTPA(Gd) nanoparticles affected the intrinsic biomechanical properties of U251 glioma cells, such as cell stiffness, adhesion, and generated traction forces, and significantly reduced the formation of protrusions, thus, exerting an inhibitory effect on their migration capacities. The results showed that the Au@DTDTPA(Gd) nanoparticles could have great interest for the therapeutic management of astrocytic tumors, not only as a radio-enhancing agent but also by reducing the invasive potential of glioma cells [115].…”
Section: Applications In Cancer Treatmentmentioning
confidence: 99%